Rancangan Sistem Informasi Manufaktur Terintegrasi untuk Mempercepat Waktu Pengiriman Produk - Taufiq, Ahmad; Sayidah, Nur (Jurnal Widya Manajemen & Akuntansi, 2005)
PT Boma Bisma Indra (BBI) b manufacturing company with make-to-order (MTO) production strategy. This research designs manufacturing information system to make integration between proposal and product realization process by using database and information network digitally at BBI. BBI has a product delivery problem. Based on current reality tree (CRT) this problem is caused by tardy of information stream from one function to the other functions.